First Report of Ventriculoperitoneal Shunt Infection due to Cyberlindnera fabianii - Jonathan Baghdadi; Peera Hemarajata; Romney Humphries; Theodoros Kelesidis (Case Reports in Infectious Diseases)
Fungal infections in the central nervous system (CNS) are associated with significant morbidity and death. Transient fungemia in immunocompetent patients without any other risk factors for fungemia has been suggested as a possible mechanism that may lead to serious fungal ventriculoperitoneal (VP) shunt infections, but evidence is lacking. The clinical spectrum, diagnosis, and optimal therapy of Cyberlindnera fabianii infections remain to be determined. We describe the first case of CNS infection due to C. fabianii that occurred in an immunocompetent adult with a VP shunt. Spontaneous translocation with yeast that is not part of the normal gastrointestinal flora in the setting of ingestion of multiple servings of a fermentation product was the likely source from which Cyberlindnera fabianii gained entrance into the VP shunt system, causing meningitis in this patient. The authors conclude that, in view of the high morbidity associated with yeast infection of the CNS, long-term antifungal therapy should be strongly considered in cases where the VP shunt cannot be completely removed. Transient fungemia may lead to invasive disease in an immunocompetent host with VP shunt, even in the absence of any other risk factors for fungemia and even after remote placement of the VP shunt.